1995
DOI: 10.1016/s0021-9975(05)80066-0
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of equine respiratory disease occurring in association with transport

Abstract: Eight young thoroughbred horses, taken 1858 km by road (travelling time, 41 h), were examined to assess the pathological nature of respiratory disease associated with transport. Three of the horses showed clinical abnormalities including pyrexia, coughing, leucocytosis and neutrophilia after the first 20 h of transportation. Endoscopical examination of the trachea revealed exacerbation of airway inflammation as a result of transport in two of the three affected horses. A consistent finding in the affected hors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
89
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 7 publications
3
89
0
Order By: Relevance
“…This finding agreed with histopathological studies by Oikawa et al [24] on equine acute respiratory disease associated with transport. The propensity of right sided-lesions is thought to be attributable to the branching of the right principal bronchus, which passes caudolaterally with a relatively straight continuation of the trachea as compared with the left principal bronchus, which runs at a more acute angle [30], forming deposition to the right side.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding agreed with histopathological studies by Oikawa et al [24] on equine acute respiratory disease associated with transport. The propensity of right sided-lesions is thought to be attributable to the branching of the right principal bronchus, which passes caudolaterally with a relatively straight continuation of the trachea as compared with the left principal bronchus, which runs at a more acute angle [30], forming deposition to the right side.…”
Section: Discussionsupporting
confidence: 93%
“…Oda et al [22] also demonstrated that activating neutrophils stimulates the secretion of pulmonary surfactant and that the stimulation is mediated by oxygen radicals. Ultrastructurally, Oikawa et al [24] observed that in pneumonic lesions in horses, alveolar cells showed edematous swelling and alveolar spaces contained material originating from lamellar inclusions stored in alveolar type II epithelial cells. In this study, therefore, we interpreted the decrease in pulmonary surfactant at admission as possibility resulting from reduction in surfactant production or exhaustion of the type II cells following a transient increase in secretion of surfactant caused by the initial inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…zooepidemicus) is a commensal bacterium of the pharyngeal tonsils and nasopharyngeal mucosa of horses [1,2]. However, opportunistic infections by this organism of the respiratory, intestinal and reproductive tracts have been reported [1][2][3]6]. This bacterium can be a causative agent of purulent rhinitis, bronchitis or pne umonia in horses under stress caused by transportation or virus infections.…”
mentioning
confidence: 99%
“…The former bacterial group tended to be more sensitive to cephalotine and gentamicin than the later bacterial group. S. zooepidemicus has been described as the bacterium isolated most frequently in respiratory diseases of horses [1,4,12,15]. In this study, S. zooepidemicus was also isolated at the highest percentage (39.5%) from BALF taken from racehorses with pneumonia associated with transport.…”
mentioning
confidence: 54%